2016
DOI: 10.1177/1461444816662933
|View full text |Cite
|
Sign up to set email alerts
|

Uses and Gratifications factors for social media use in teaching: Instructors’ perspectives

Abstract: This research was motivated by an interest in understanding how social media are applied in teaching in higher education. Data were collected using an online questionnaire, completed by 333 instructors in higher education, that asked about general social media use and specific use in teaching. Education and learning theories suggest three potential reasons for instructors to use social media in their teaching: (1) exposing students to practices, (2) extending the range of the learning environment, and (3) prom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 33 publications
0
48
0
3
Order By: Relevance
“…For example, using a learning management system (LMS) is dependent on provision by the institution, and it requires time and skill to build course sites. Social media integration occurs when instructors have value for it in teaching and in learning (MMS Education, ) and align it with instructional goals (Gruzd, Haythornthwaite, Paulin, Gilbert, & del Valle, ). In this study, more than one‐fifth of respondents indicated that an LMS was not available to them and 10% had no access to social networking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using a learning management system (LMS) is dependent on provision by the institution, and it requires time and skill to build course sites. Social media integration occurs when instructors have value for it in teaching and in learning (MMS Education, ) and align it with instructional goals (Gruzd, Haythornthwaite, Paulin, Gilbert, & del Valle, ). In this study, more than one‐fifth of respondents indicated that an LMS was not available to them and 10% had no access to social networking.…”
Section: Discussionmentioning
confidence: 99%
“…Other data from our questionnaire suggest a reason for this. In our previous study, we found overwhelmingly that current users were adopting social media not provided within the university learning management systems ( [23]). Thus, lack of internal technical support is a non-issue for current use as reported by these participants, but can be seen to be a barrier to future use.…”
Section: Discussionmentioning
confidence: 99%
“…In our initial study using data from the questionnaire reported here [23], qualitative coding of answers to questions about social media use and usefulness for teaching were analyzed in light of three theoretical reasons that emerge from education and learning theories and suggest why instructors may seek to introduce social media into their classes in support of teaching and learning: exposing students to practice; extending the learning environment; and promoting a social, collaborative approach to learning. Results of a Principal Component Factor Analysis of the coded data identified six ways social media were used for teaching (60% of total variance explained; variance per factor 8-13%): (1) Facilitating Engagement through student participation and reflection; (2) Organizing for Teaching by facilitating the organization of teaching activities; (3) Reaching Outside to connect the class experience to knowledge and work outside the classroom; (4) Enhancing Student Learning by using social media as a way to enhance further evaluation of class content; (5) Building a Community of Practice by fostering communities among students; and (6) Discovery of relevant information by instructors and students.…”
Section: Faculty Use Of Social Media For Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Esteve del Valle, Gruzd, Haythornthwaite, Paulin, and Gilbert () surveyed faculty regarding their teaching with social media and found a wide range of media use, including social networking sites (SNS), multimedia repositories, document sharing, wikis, microblogging, blogs, academic SNS, presentation sharing and social bookmarking. Faculty described six major purposes: (a) facilitating engagement via peer interaction and reflective learning; (b) organization for teaching via sharing by instructor and discussion; (c) reaching outside the class and learning about social media through practice; (d) enhancing student learning through supporting collaboration; (e) building a community of practice; and (f) discovery by students and instructor (Gruzd, Haythornthwaite, Paulin, Gilbert, & Esteve del Valle, ).…”
Section: Social Media In Academiamentioning
confidence: 99%